PROBLEMS AND POETICS OF SOCIAL PLAYS BY LYUDMILA STARITSKA-CHERNIAHIVSKA - Процюк, Л. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with theproblematics and poetics of Lyudmila Starytska-Cherniahivska's playson social theams. Attention is paid to the dramatic works of"Wings" and "Musicians of theUkrainian word". The analysis of the problems and specifics of the conflict is carried out.